Bioactivity of catalase loaded into vaterite CaCO3 crystals via adsorption and co-synthesis - Feoktistova, Natalia A.; Vikulina, Anna S.; Balabushevich, Nadezhda G.; Skirtach, Andre G.; Volodkin, Dmitry (Materials & Design, 2020)
Protein therapy gained a reputation of the most direct and safe approach for treating various diseases, yet biodegradation and loss of bioactivity of fragile therapeutic proteins limit their wide medical use. Recently, a new hard templating technology using decomposable mesoporous vaterite CaCO3 crystals became extremely popular strategy for formulation of protein nano(micro)-vectors. This study deciphers how protein bioactivity depends on protein loading/release for this technology utilizing catalase as a promising antioxidant therapeutic agent. Catalase has been loaded into CaCO3 using two approaches: i) passive - via adsorption (ADS) into pre-formed crystals and ii) active - via co-synthesis (COS) in the pH range 8–10. Crystal morphology, protein secondary structure and enzymatic bioactivity, and protein retention upon washing are assessed. The activity reduction (∼70% for COS and ∼20% for ADS) is caused by both protein exposure to an alkaline medium and protein aggregation induced by Ca2+. The aggregation significantly governs protein release kinetics. Catalase loading into the crystals is pH-independent and van der Waals interactions dominate over the electrostatics, while catalase activity strongly depends on pH. This study implicates the prime role of loading/release mechanism in the preservation of protein bioactivity and guide for the control over the retention of protein bioactivity.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Calcium carbonate; Circular dichroism; Co-synthesis; Encapsulation; Mesoporous